2013
DOI: 10.4187/respcare.02978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mask Dead Space and Occlusion of Mask Holes on Delivery of Nebulized Albuterol

Abstract: , and adult (V T ‫؍‬ 500 mL, breathing frequency ‫؍‬ 15 breaths/min, I:E ‫؍‬ 1:2) breathing patterns was connected to a collection filter hidden behind a face plate. A pediatric size mask and an adult size mask connected to a continuous output jet nebulizer were sealed to the face plate. Three nebulizers were loaded with albuterol sulfate (2.5 mg/3 mL) and operated with 6 L/min compressed air for 5 min. Experiments were repeated with different degrees of occlusion (0%, 50%, and 90%). Albuterol was extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…7,14 The breathing pattern with the lowest tidal volume (50 mL) had a lung dose that was lower than with the other breathing patterns (155 and 300 mL), which were similar. This could be explained by the fact that both breathing patterns had an inspiratory flow (tidal volume/inspiratory time ϫ 60) that exceeded the nebulizer flow (11.6 and 22.5 L/min, respectively).…”
Section: Discussionsupporting
confidence: 52%
“…7,14 The breathing pattern with the lowest tidal volume (50 mL) had a lung dose that was lower than with the other breathing patterns (155 and 300 mL), which were similar. This could be explained by the fact that both breathing patterns had an inspiratory flow (tidal volume/inspiratory time ϫ 60) that exceeded the nebulizer flow (11.6 and 22.5 L/min, respectively).…”
Section: Discussionsupporting
confidence: 52%
“…This finding is in agreement with another study that showed that decreasing the dead space of the mask in nebulized therapy did not increase the amount of aerosol captured at the mouth opening. 19 …”
Section: Interfacesmentioning
confidence: 99%
“…[15][16][17][18] Higher tidal volumes (V T ) are associated with higher intrapulmonary deposition. 19 On the other hand, behavioral challenges are crucial in infants and young children. Crying and lack of proper mask seal are known to decrease intrapulmonary deposition.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 They can be instructed to switch off after a predetermined dose has been delivered and can provide operational logs regarding patient adherence to prescribed treatment. 45,47 Soft mist inhalers Continued innovation in inhaler technology has led to a new class of inhaler device called SMIs. 50 SMIs transform aqueous liquid solution to an inhalable vapour using the energy of a compressed spring inside the inhaler.…”
Section: Nebulisersmentioning
confidence: 99%
“…44 They are also useful for infants and children where the aerosol can be delivered via a facemask. 45 The most common type of nebuliser is the jet or pneumatic nebuliser, which uses compressed air to generate the aerosol. They are relatively cheap but because of their need for compressed air they can be quite bulky and noisy.…”
Section: Nebulisersmentioning
confidence: 99%